Restoration history of the main church in Breda (Bulletin KNOB, 2010)
The main church in Breda is known as one of the most complete late Gothic town churches in the Netherlands. The cruciform basilica with tall west tower and ambulatory is considered an ideal example of a type of church that for various reasons was never completed in many other Dutch towns. The building history shows that in reality this perfect unity of design was realized by changing plans a number of times. In various periods several commissioners wanted to leave their mark on the church. After having changed users several times in the period of the Reformation, in the early 17th century a period of maintenance started without large new construction or alterations. In this respect it is striking that maintenance or restoration was executed by reusing old building material as much as possible and by carefully preserving old forms.In spite of the outmoded design the building was generally regarded as the pride of the town. Only the fire in the tower in 1694 forced the town administration to have a new wooden steeple built. After in the course of the 18th century it had become more and more difficult to pay for the maintenance, in the early 19th century a period of serious neglect began due to the separation of Church and State and the severe economic decline. This did not come to an end until from 1874 onwards structural financial support was given by the State, province and municipality. In various stages a restoration starts whereby all the parties involved continued to profess the wellknown restoration starting point of ‘preservation has priority over restoration’.In practice, however, architects like Van Nieukerken and government inspectors like P.J.H. Cuypers regularly proved to consider their own vision on the building more important than the clues contained in the building itself. Important choices for restoring – whether or not disappeared – ornaments, seldom occurred on the basis of building-historical research, although both strongly recommended it. It is striking that the basically less schooled local architect A.J.F. Cuypers was more inclined to respect the existing. When he added or interpreted, this was done in a distinctly individual style, so that later consideration of his work gives a relatively clear impression of what his influence on the building was. This caused him much criticism and eventually his discharge from the commission.Because of all these fundamental restorations the building was saved from certain ruin, but in the details of the exterior it is largely a sum of various 19th- and 20th-century interpretations.